2023
DOI: 10.1002/pmh.1578
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and personality functioning interact substantially in predicting depression, anxiety, and somatization

Abstract: Etiological theories on the development of psychopathology often incorporate adverse childhood experiences (ACE) as an important contributing factor. Recent studies suggest personality functioning (PF; i.e., stability of the self and interpersonal relationships) as an important transdiagnostic construct that could be useful in better understanding when persons with ACE do (not) develop psychopathological symptoms. A representative sample of N = 2363 was assessed by questionnaires on ACE, PF (Level of Personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 75 publications
2
2
0
Order By: Relevance
“…Our findings are partially consistent with the recent study by Kerber et al. (2023), in which ACEs and personality functioning were examined as predictors of anxiety symptoms, depressiveness, and somatization ( 36 ). In this cross-sectional study, while it was shown that ACEs were positively associated with psychopathology, an association between ACEs and impairments of personality functioning was also found.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are partially consistent with the recent study by Kerber et al. (2023), in which ACEs and personality functioning were examined as predictors of anxiety symptoms, depressiveness, and somatization ( 36 ). In this cross-sectional study, while it was shown that ACEs were positively associated with psychopathology, an association between ACEs and impairments of personality functioning was also found.…”
Section: Discussionsupporting
confidence: 93%
“…Aside from the findings that both ACEs and personality functioning are each associated with treatment outcome in psychotherapy, ACEs have repeatedly been linked to personality functioning ( 23 , 31 35 ). For example, it was found that the interaction between ACE and personality functioning predicts psychopathology, including anxiety symptoms ( 36 ). Assessing a heterogeneous sample of psychotherapy patients, Kindermann et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, we found no direct effects of personality functioning on improvement rate in psychotherapy. Our ndings are partially consistent with the recent study by Kerber et al (2023), in which ACEs and personality functioning were examined as predictors of anxiety symptoms, depressiveness, and somatization [36]. In this cross-sectional study, while it was shown that ACEs were positively associated with psychopathology, an association between ACEs and impairments of personality functioning was also found.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike personality traits, which describe how individuals are, personality functioning (PF) focuses on basic psychological capacities individuals possess in perception, regulation, communication, and relationship formation to interact with themselves and the social world [18]. This de nition of PF draws on objects relations and mentalization theories [14], which postulate that de cits in regulating the self and relationships (i.e., low levels of PF) are a result of adverse geneenvironment interactions in early childhood and predispose individuals to psychopathology in general [19]. Empirically, PF shows less longitudinal stability in mean levels compared to personality traits, except for neuroticism [20], which overlaps signi cantly with PF [21] and appears more responsive to clinical interventions than other traits [22].…”
Section: Personality Functioning (Pf) and Hitopmentioning
confidence: 99%